1983
DOI: 10.2134/agronj1983.00021962007500030002x
|View full text |Cite
|
Sign up to set email alerts
|

Fertilizer Nitrogen Utilization by Corn, Tomato, and Sugarbeet1

Abstract: Differences in the abilities of crops to utilize fertilizer and soil N can contribute to the establishment of rotation systems to improve the efficiency of fertilizer use and reduce nitrate pollution groundwater. Field studies show considerable site variability in the utilization of fertilizer by individual crops. To compare fertilizer N use by corn (Zea mays L.), sugarbeet (Beta vulgaris L.), and tomato (Lycopersicon esculentum Mill.), several rates of fertilizer N were applied to replicated plots of each cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0
1

Year Published

1990
1990
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 2 publications
2
29
0
1
Order By: Relevance
“…Reported values of total N uptake by processing tomatoes usually range from 150 to 300 kg N ha -I depending on cultivar, soil, and irrigation system (Broadbent et al, 1980;Hills et al, 1983;Tesi and Giustiniani, 1987). Because of its short season (4-5 month), tomato N uptake rates can be as high as 4.3 kg N ha -1 day -1 (Dumas, 1990).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reported values of total N uptake by processing tomatoes usually range from 150 to 300 kg N ha -I depending on cultivar, soil, and irrigation system (Broadbent et al, 1980;Hills et al, 1983;Tesi and Giustiniani, 1987). Because of its short season (4-5 month), tomato N uptake rates can be as high as 4.3 kg N ha -1 day -1 (Dumas, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Because of its short season (4-5 month), tomato N uptake rates can be as high as 4.3 kg N ha -1 day -1 (Dumas, 1990). Processing tomatoes are considered to have low fertilizer N use efficiency, with values usually lower than 40%, and soil derived N is considered a major source for this crop (Broadbent et al, 1980;Hills et at., 1983;Miller et al, 1981).…”
Section: Introductionmentioning
confidence: 99%
“…For example, addition of more than 50 kg N ha-1 gave no significant increase in yield (Broadbent et al, 1980), and at 100 kg N ha -1 (ammonium sulfate), tomato only recovered about 20 percent of fertilizer N (Hills et al, 1983). Absorption of fertilizer N is greatest when residual soil N levels are low, and when the direction of irrigation water movement carries bands of fertilizer toward the plant (Miller et al, 1981).…”
Section: Introductionmentioning
confidence: 99%
“…Another study in the US showed for 10 Tonne.ha-1 root, leaves absorb 20 kgN.ha-1 and for 10 Tonne.ha-1 root and shoot production 40-55 kg N.ha-1 needed (Buchner & Sturm, 1985). half amount to produce the same amount of root needed (Hills et al, 1983). In another study, it showed that 5 kg of N is needed to produce each Tone of Root (Eckhoff & Flynn, 2008).…”
Section: Issn-2348 5191 (Print) and 2348 8980 (Electronic)mentioning
confidence: 96%
“…Improvement in fertilizer implication method can increase NUE (Sowers et al, 1994, Good et al, 2004 but other approaches like UTE and UPE improvement may be helpful to reach the Goal (Hills et al, 1983). Some studies showed that in an excess amount of Nitrogen, UPE gains more importance, however, at the times of Nitrogen scarcity, UTE has the main importance.…”
Section: Issn-2348 5191 (Print) and 2348 8980 (Electronic)mentioning
confidence: 99%